Yarn-ball-shaped CNF/MWCNT microspheres intercalating Ti3C2Tx MXene for electromagnetic interference shielding films. (15th February 2021) - Qian, Kunpeng; Wu, Hongmin; Fang, Jianhui; Yang, Yuhuan; Miao, Miao; Cao, Shaomei; Shi, Liyi; Feng, Xin
Highlights: Ti3 C2 Tx MXene intercalated with yarn-ball-shaped microspheres for EMI shielding. Yarn-ball-shaped microspheres provide more reflection interfaces in hybrid films. Films with hierarchical structure are conducive causing more absorption of EMW. The EMI shielding films exhibit excellent mechanical robustness and durability. Abstract: Ti3 C2 Tx MXenes with excellent metallic conductivity have proved promising in its application of electromagnetic interference (EMI) shielding. A hierarchical hybrid film with ultrathin thickness composed of Ti3 C2 Tx MXene layers embedded with yarn-ball-shaped microspheres of cellulose nanofibrils (CNF) and multiwalled carbon nanotube (MWCNT) was designed to improve the absorption of electromagnetic waves (EMWs). The addition of yarn-ball-shaped microspheres is to shield more EMWs via multiple reflections in the inner space and reduce the undesirable emissions into the air. After thermal annealing treatment, the ultrathin film with intercalation of the carbonized yarn-ball-shaped CNF/MWCNT microspheres exhibited enhanced EMWs absorption as an important part of shielding effectiveness (45.1±0.9 dB) as well as excellent mechanical stability (≈0.9 million bending times). Thus, the well-designed structure of multilayered hybrid films with intercalated conductive microspheres can be a good candidate for higher absorption in EMI shielding effectiveness and outstanding mechanical properties.